SAT-218 Hypothalamic-Pituitary-Gonadal (HPG) and Hypothalamic-Pituitary-Adrenal (HPA) Axis Responsiveness in Women and Men during 29 Weeks of Basic Military Training - Gifford, Robert (J Endocr Soc, 2019)
Exercise-associated endocrinopathy in athletes has been attributed to low energy availability (EA). We hypothesized this would be relevant to British Army Officer training, which involves arduous exercise and non-exercise stressors. We aimed to explore changes in LH, FSH and cortisol responsiveness in women and in a smaller cohort of men over 29 weeks of basic military training. We studied fifty-six Officer Cadets (age 24.4 ± 2.5 years, 47 female: combined contraceptive pill users (CCP, n=14), progestogen-only users (PROG, n=16), and non-contraceptive and intrauterine device users (NONE, n=17)) on entering (week (w)1) and completing (w29) training. Body composition was measured by DXA and average monthly hair cortisol by LC-MS. A combined low dose 10µg GnRH and 1.0µg ACTH-(1-24) test was performed with LH, FSH and cortisol measured by LC-MS at baseline, 20, 30 and 60 mins. For cortisol analyses, PROG and NONE groups were considered seperately (as PROG/NONE), due to CCP increasing CBG. Weight increased in both women and men over the training period (mean ±SD, 64.4 ±7.4 kg vs 65.3 ±7.2 kg, p=0.05 and 84.5 ±7.4 kg vs 87.0 ±9.1 kg, p=0.02, respectively), comprising increased fat but not lean mass. Menstrual cyclicity in NONE was unchanged. Training blunted the peak LH- and FSH-foldwise response to GnRH in women (median [IQR] 5.74 [3.23, 19.7] vs 3.44 [2.62, 6.51], p=0.002 and 1.65 [1.37, 2.37] vs 1.39 [1.25, 1.77], p=0.005, respectively) but not men (4.28 [2.92, 4.73] vs 3.29 [2.34, 5.78], p=0.5 and 1.46 [1.30, 1.56] vs 1.34 [1.21, 1.51], p=0.6, respectively). Hair cortisol was higher in women than men over the 3 months before training (median (IQR) 7.71 (3.85, 16.0) pg/mg vs 3.53 (2.95, 5.89) pg/mg, p<0.0001) and remained higher in women in the final 3 months of training (8.18 (3.61, 10.37) vs 3.38 (2.38, 5.79) pg/mg, p=0.001). Basal cortisol tended to be lower among PROG/NONE than males in w1 (177 ± 91.9 vs 313 ±92.9 nmol/l, p=0.08), but increased by w29 in PROG/NONE but not men (to 259 ±103 nmol/l; p=0.003 vs to 246 ±187 nmol/l; p=0.4, respectively). Cortisol response to ACTH was blunted in PROG/NONE (peak foldwise increase 3.83 ±1.5 vs 2.84 ±1.0, p=0.048) but was unchanged in men (2.96 ±0.9 vs 2.46 ±0.9, p=0.3). No significant cortisol changes were seen in CCP.The elevated hair cortisol in women may represent greater anticipatory response than men. Hair and basal plasma cortisol increased in women compared to men in response to training, though LH, FSH and cortisol responsiveness in women was blunted. While our findings are broadly in accord with previous reports of exercise and training-associated pituitary and adrenal suppression, our novel finding is that this was not associated with evidence of low EA in our population. We propose endocrine changes in arduous training reflect complex interactions of sex and stressors with the HPA and HPG axes.